Analyzing customer satisfaction: users perspective towards online shopping. Issue 3 (7th August 2017) - Tandon, Urvashi; Kiran, Ravi; Sah, Ash
Abstract : Purpose: This study aims to identify and analyse the key determinants influencing customer satisfaction towards online shopping in India. Design/methodology/approach: The literature concerning major attributes of website functionality, perceived usability, perceived usefulness and customer satisfaction in online retailing were reviewed. Data were collected from 365 respondents active in online shopping for examining the constructs. The model was empirically tested using structural equation modelling. Findings: The findings of the study reveal that perceived usefulness and website functionality have a positive impact on customer satisfaction, whereas perceived usability had a significant but negative impact on customer satisfaction. Practical implications: This research will help online retailers to attract and motivate new customers for online shopping and existing customers to extend it in their daily purchase. Online retailers can improve post purchase satisfaction and eventually increase online customers. Originality/value: This is one of the preliminary study dealing with customer satisfaction towards online retailing in India. The scale has been extended to include items like satisfaction with cash on delivery mode of payment not included in previous scales. The scale of perceived usefulness has also been deepened by adding time performance, product performance and promotional performance.